Food intake: an overlooked driver of climate change casualties?. (August 2021) - Youngentob, Kara N.; Lindenmayer, David B.; Marsh, Karen J.; Krockenberger, Andrew K.; Foley, William J.
Abstract : Reduced voluntary food intake is a common response of endotherms to warmer temperatures. However, the implications of this are rarely considered for wild animals exposed to higher temperatures caused by climate change. We provide a conceptual model to demonstrate the potential consequences of elevated temperatures on food intake and survival.